2006
DOI: 10.1007/s11107-006-5321-3
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Diverse Routing in Wavelength-Routed Networks with Shared Risk Link Groups

Abstract: In this paper, we consider path protection in wavelength-routed networks with shared risk link groups (SRLGs). Specifically, we study diverse routing, where two paths without sharing any SRLG have to be found between each pair of source-destination nodes, and its applications in dynamic shared protection as well. For the NP-complete diverse routing problem, a heuristic method is proposed, which steadily outperforms an existing algorithm within the first few iterations. When more iterations of calculations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This algorithm allows for an improvement on the resource utilization ratio (as bandwidth resources are shared among BPs) and for the consideration of differentiated reliability (DiR) requirements of different customers. A shared protection context is also considered in [18]. A hybrid protection scheme is proposed in [21], where shared-path and sharedlink protections are jointly used in WDM networks with SRLGs.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm allows for an improvement on the resource utilization ratio (as bandwidth resources are shared among BPs) and for the consideration of differentiated reliability (DiR) requirements of different customers. A shared protection context is also considered in [18]. A hybrid protection scheme is proposed in [21], where shared-path and sharedlink protections are jointly used in WDM networks with SRLGs.…”
Section: Introductionmentioning
confidence: 99%
“…An algorithm based on the algorithm CoSE, in [11], for solving the min-sum SRLG diverse routing problem, enabling the calculation of an extremely high percentage of optimal solutions in short times, is proposed in [19]. In [20], the problem of path protection in wavelength-routed networks with SRLG, is addressed and a heuristic method is developed and compared with the trap avoidance algorithm in [21]. Note that the original SRLG diverse routing type problems gave rise to a significant number of variants, not addressed here, specially related to the constraints of the problem, in particular the nature of protection schemes, focused on the treatment of bandwidth in the AP/BP paths (where, typically, dedicated protection or shared protection schemes may be used) and the type of objective function(s) to be optimized.…”
Section: Introduction and Motivation 1introduction And Related Workmentioning
confidence: 99%
“…The heuristic proposed in [23] for solving this problem is an improvement of the Iterative Two-Step Approach (ITSA) [10]. In [19,20] the authors considered the problem of path protection in wavelength-routed networks with SRLGs, proposed a heuristic method, which they compared with the Trap Avoidance (TA) algorithm [25]. They concluded that the new algorithm, Minimum Total Weight (MTW), outperforms TA within the first few iterations.…”
Section: Introductionmentioning
confidence: 99%